2022
DOI: 10.1111/ijac.14038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tool coating materials and coating thickness on cutting temperature distribution with coated tools

Abstract: Coated tools are currently widely used tool technology in machining. The influence of tool coating on heat transfer has become an active field of research enjoying constantly increasing attention in the field of machining. This paper is devoted to the cutting temperature in machining H13 hardened steel with monolayer coated tools (TiN, TiAlN, and Al2O3) and multilayer coated tools (TiN/TiC/TiN and TiAlN/TiN). Equivalent composite thermal conductivity and thermal diffusivity of multilayer coated tools were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Coated cemented carbide tools are an ideal tool for the precision machining of hardened steel due to their high oxidation and bond resistance, which reduce friction and heat between the tool and the machined material. 11 Ghani et al 12 investigated the properties of TiN-coated tools in the precision machining of AISI H13 steel under high-speed cutting conditions. The study revealed that a favorable surface roughness of approximately .4 μm was achieved with a cutting depth of .3 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coated cemented carbide tools are an ideal tool for the precision machining of hardened steel due to their high oxidation and bond resistance, which reduce friction and heat between the tool and the machined material. 11 Ghani et al 12 investigated the properties of TiN-coated tools in the precision machining of AISI H13 steel under high-speed cutting conditions. The study revealed that a favorable surface roughness of approximately .4 μm was achieved with a cutting depth of .3 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Coated cemented carbide tools are an ideal tool for the precision machining of hardened steel due to their high oxidation and bond resistance, which reduce friction and heat between the tool and the machined material 11 . Ghani et al 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang Shijun et al [7] proposed a new approach to improve the prediction of the temperature of coated cutting tools, resulting in a model that can be used to design coated tools. Jingjie Zhang et al [8] studied the effect of tool coating materials and coating thickness on the distribution of cutting temperature with coated tools, and observed that cutting temperature decreases with the increase in coating thickness of the same type. Moreover, they concluded that thermal conductivity and diffusion affect cutting temperature in transient and steady heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic coatings have extensive applications in cutting tools due to the higher hardness, wear resistance, and thermal stability [1]. For example, Al 2 O 3 -coated tools can effectively improve machining efficiency and machining accuracy [2,3].…”
Section: Introductionmentioning
confidence: 99%